2009
DOI: 10.1111/j.1439-0310.2008.01591.x
|View full text |Cite
|
Sign up to set email alerts
|

A Statistical Modelling Approach to the Occurrence and Timing of Reconciliation in Wild Japanese Macaques

Abstract: In various social species, animals have been observed to share friendly relationships with some group members and to resolve conflicts through reconciliation, the exchange of affiliative behaviour soon after a conflict that functions to restore the relationship between the former opponents. The valuable relationship hypothesis predicts that reconciliation should be observed more often after conflicts between friends. Friendly relationships can be described by three dimensions (i.e. value, security and compatib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 47 publications
(147 reference statements)
5
40
1
2
Order By: Relevance
“…These results are in agreement with the idea that the value of a relationship is the most important determinant of conflict resolution, while compatibility and security play a less relevant role [Majolo et al, 2009]. Despite recent efforts to group different measures of social interactions into the three dimensions of relationship quality [Fraser et al, 2008], further studies are needed to examine the consistency of these results in other species.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…These results are in agreement with the idea that the value of a relationship is the most important determinant of conflict resolution, while compatibility and security play a less relevant role [Majolo et al, 2009]. Despite recent efforts to group different measures of social interactions into the three dimensions of relationship quality [Fraser et al, 2008], further studies are needed to examine the consistency of these results in other species.…”
Section: Discussionsupporting
confidence: 78%
“…Social relationship variables, together with dominance ranks, were computed separately for 2004 and 2005 data. Social variables were assigned to the different dimensions of relationship quality according to Fraser et al [2008] and Majolo et al [2009]. Both studies use grooming reciprocation as an indicator of relationship security.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The likelihood and timing of reconciliation are known to be influenced by the characteristics of conflicts, that is, duration, intensity, occurrence of intervention, decidedness of outcome, and those of the opponents, that is, sex, age and dominance rank (Aureli et al 1989;Call et al 1999;Arnold & Aureli 2007;Majolo et al 2009a). A multivariate approach showed that quadratic affiliation in Tonkean macaques occurred earlier after conflicts involving physical contact.…”
Section: Discussionmentioning
confidence: 99%
“…集団で生活する霊長類は,複雑な社会の中で生活を している。霊長類の社会行動を研究する場合,血縁や 順位,親密さといった要因が注目される。例えば,集 団の各個体間には優劣関係があり,劣位個体は優位個 体に多く毛づくろいをする傾向があると指摘されてい る (Seyfarth, 1977;Schino, 2001; 上野 , 2016) 。 し か し, すべての個体がそのように行動するわけではなく,優 劣関係が比較的明瞭なニホンザル(Macaca fuscata)集 団の中にも,優位個体から劣位個体に毛づくろいを多 く行う個体がいる (Nakamichi & Shizawa, 2003 (Koyama, 2001) 。血縁個体間や,普段近接や毛づくろいをするこ との多い個体との間で攻撃が生じた場合には,比較的 高い割合で仲直り行動が行われる (Kutsukake & Castle, 2001;Majolo et al, 2009) 。このような知見から,攻撃交 渉の直後に行われる毛づくろい等の行動は,攻撃交渉 によって損なわれた社会関係を修復する機能を持つと 考えられている (Aureli et al, 2002) 。 しかし,霊長類の「仲直り」が,どの行動によって 成立しているのかに関しては疑問の余地がある (Silk et al, 1996) (Tanaka & Takefushi, 1993;Zamma, 2002) et al, 1999;Ueno et al, 2015) Parton et al(2009) …”
Section: 霊長類の社会行動研究unclassified